CLINICAL, EPIDEMIOLOGICAL, LABORATORY AND IMAGING ASPECTS OF BRUCELLOSIS WITH AND WITHOUT NEUROLOGICAL INVOLVEMEN - M. Ghaffarpour; A. Khoshroo; M. H. Harirchian; H. Sikaroodi; H. Pourmahmoodian; S. Jafari S. S. Hejazi (Acta Medica Iranica, 2007)
Brucellosis is an endemic disease in our country. Neurobrucellosis occurs in 5 to 10% of cases, and can present at any stage of of the disease. This study was undertaken to evaluate clinical, epidemiological and paraclinical aspects of brucellosis with and without neurological manifestations. Data of 30 patients, 15 cases with nervous system involvement (neurobrucellosis) and 15 cases without neurological complication (brucellosis) were collected and analyzed. Constitutional manifestations of the disease were detected with nearly the same frequencies in both groups. Exceptions were headache which was more common in patients with neurobrucellosis (73% vs. 33%) and arthralgia which was detected more frequently in cases with brucellosis than neurobrucellosis (53% vs. 13%). Signs and symptoms of meningeal irritation and disturbances of consciousness were the most common manifestations in cases with neurobrullosis, which had been detected in 60% and 46.7% of cases, respectively. Less common neurological presentations, in decreasing order of frequency were ophthalmoplegia, papilledema and seizures, spastic weakness of limbs, hearing loss and spinal epidural abscess. In two patients with negative serum and CSF agglutinin test, diagnosis of neurobrucellosis was made by blood and CSF cultures. In patients with neurobrucellosis, MRI of brain and spinal cord showed abnormalities in 5/15(33.3%) of cases, including decreased lateral ventricular volume due to brain swelling (2/15), hydrocephalus with periventricular edema and meningeal enhancement in posterior fossa (1/15), multiple hypodense periventricular lesions, ischemic or demyelinating in nature (1/15) and spinal epidural abscess (1/15). Brucellosis should be kept in mind in patients with neurological presentations.